Paradigma Administrasi Pendidikan di Indonesia Era Disrupsi 4.0 - Atik Likai Tanjua; Okta Viani; Afindi Afindi (Al-Khair Journal: Management Education, 2025)
Abstract: Educational administration still creates difficulties in entering the development of digital science and technology, marked by the fact that there are still human resources who are unable to upgrade their digital literacy knowledge such as data literacy, technological literacy and mechanical literacy in the world of work. The purpose of this study is to map and describe the paradigm of educational administration in Indonesia in the era of disruption 4.0. Using a literature review method, this study examines educational administration transforming along with technological advances, such as artificial intelligence (AI), the internet of things (IoT), and digital systems.The results of the study show that educational administration in the 4.0 era can generally integrate digital literacy in the 4.0 disruption era, including the management of student administration, personnel, curriculum, facilities and infrastructure, finance, and school relations with the community. In the 4.0 disruption era, educational administration faces major challenges, especially in mastering information technology, digital literacy, and critical thinking skills.Educational administration has not been able to adapt to technological changes and integrate digital tools to improve its efficiency and effectiveness. So it can be concluded that the paradigm of educational administration in Indonesia is generally quite good but not yet optimal in its implementation. Therefore, it can be suggested that in order to improve digital literacy, we need to integrate the paradigm of educational administration in Indonesia in the era of disruption.Keywords: Paradigm, Educational Administration, Era of Disruption 4.0. Abstrak: Administrasi pendidikan masih menciptakan kesulitan memasuki perkembangan ilmu pengetahuan dan teknologi digital, ditandai masih terdapat sumberdaya manusia yang tidak mampu mengupgrade pengetahuan literasi digital seperti literasi data, literasi teknologi dan literasi mkanika dunia kerja. Tujuan penelitian ini untuk memetakan dan mendeskripsikan paradigma administrasi pendidikan di Indonesia era disrupsi 4.0. Menggunakan metode kajian pustaka, penelitian ini mengkaji tentang administrasi pendidikan bertransformasi seiring dengan kemajuan teknologi, seperti kecerdasan buatan (AI), internet of things (IoT), dan sistem digital. Hasil penelitian menunjukkan bahwa administrasi pendidikan di era 4.0 secara umum dapat mengintegrasikan literasi digital di era disrupsi 4.0, mencakup pengelolaan administrasi peserta didik, personal, kurikulum, sarana dan prasarana, keuangan, serta hubungan sekolah dengan masyarakat. Era disrupsi 4.0, administrasi pendidikan menghadapi tantangan besar, terutama dalam penguasaan teknologi informasi, literasi digital, dan keterampilan berpikir kritis. Administrasi pendidikan belum mampu beradaptif terhadap perubahan teknologi dan mengintegrasikan alat digital dalam meningkatkan efisiensi dan efektivitasnya. Sehingga dapat disimpulkan bahwa paradigma administrasi pendidikan di Indonesia secara umum sudah cukup baik namun belum optimal dalam pelaksanaannya. Oleh karena itu dapat disarankan bahwa untuk dapat meningkatkan literasi digital untuk mengintegrasikan paradigma administrasi pendidikan di Indonesia era disrupsi.Kata kunci: Paradigma, Administrasi Pendidikan, Era Disrupsi 4.0.